NEW ASPECTS OF LABORATORY DIAGNOSTICS OF LIVER FIBROSIS - Nabieva Farangiz; Avazova Gulzoda; Baratova Nodira; Ergashova Shakhlo (TADQIQOTLAR, 2026)
Abstract. Currently, the mortality rate from terminal stage liver fibrosis - cirrhosis - ranks 9th in the world among all causes of death and 6th among people of working age, amounting to 14 to 30 cases per 100 thousand people. The article presents current data on the methods used for the diagnosis of liver fibrosis. To date, liver biopsy, the study of direct and indirect serological markers, as well as instrumental methods are used. Laboratory diagnosis of fibrosis at this stage of development of medicine is aimed at the development, improvement and application of non-invasive diagnostic methods. This is due to the ability to track the dynamics of the disease, the lack of contraindications and other advantages.